Seroprevalence study of Parvovirus B19 among women with miscarriage in Mosul city - Nawfal Buraa, Atheer; Baqer Al-Obaidi, Asmaa; Ali Hussein, Thekra (Diyala Journal of Medicine, 2023)
Background: Miscarriage and stillbirth are among the most common pregnancy complications, and could be caused by several factors, among these factors are viral infections some of them are obvious teratogenic and others are associated with fetal defects like severe anemia in the case of Parvovirus B19 which could be transmitted vertically causing fetal infection and miscarriage or stillbirth. Objective: To investigate the seroprevalence of Parvovirus B19 among women with miscarriage and stillbirth and compare them with normal pregnant women in the city of Mosul-Iraq. Patients and Methods: A case-control study conducted on pregnant aged 16-45 years with miscarriage and stillbirth admitted to Al-Khansa Teaching Hospital in Mousl city. The samples were collected during the period from November 2022 and January 2023 from 160 from pregnant women, 80 of them had miscarriage or stillbirth, and the other 80 had normal uneventfull pregnancy (control). Serum samples were subjected for ELISA Study of anti-B19V IgG and IgM antibodies. Results: This study showed that the seroprevalence rate of anti-B19V IgG among pregnant women was about 23% (37 out of 160), subdivided into (40%) 32 out of 80 patients, and (6.2%) 5 out of 80 controls had positive anti-B19V IgG antibody which is significantly different. And IgM seroprevalence was about 22% (35 out of 160), in which (38.8%) 31 out of 80 patients, and (5%) 4 out of 80 controls had positive anti-B19V IgM antibody. Both anti-B19V IgG and IgM were higher among patients who had stillbirth than those who had miscarriage both qualitatively and quantitatively. On the other hand, there is a highly significant association of anti-B19V IgM positivity with maternal anemia. Conclusion: The study found high association between B19V and miscarriage or stillbirth as compared to normal pregnancy, and this was more common among patients who had stillbirth than those who had miscarriage, with obvious association with maternal anemia, all of the above is among pregnant women from Mosul City in Iraq.